SELÇUKLULAR DÖNEMİNDE ASTRONOMİ - KAYA, SEYFETTİN (Fırat Üniveristesi, 2018)
İlk uygarlıklar dini, ekonomik ve siyasi aktivitelerini düzenlemek için astronomi bilimine önem vermişlerdir. Astronomi bilimi doğu uygarlıklarında kozmoloji anlayışından dolayı gelişmiştir. Özellikle Aristoteles ve Batlamyus'un yer merkezli evren anlayışı yaygın bir düşünce olarak benimsenmiştir. İslâmi Dönemde Aristoteles ve Batlamyus'un savunduğu evren anlayışı kabul edilmiştir. Ancak bu anlayışta bulunan eksiklikler tamamlanmaya ve yanlışlar düzeltilmeye çalışılmıştır. Selçuklular Dönemi'nde ise ilk uygarlıkların ve İslâm Dünyası'nın benimsediği astronomi anlayışında çok fazla bir değişiklik yapılmamıştır. Aristoteles ve Batlamyus'un evren ve astronomi anlayışı devam ettirilmiştir. Ancak bu dönemde Batlamyus'un eserleri eleştirilmiş ve söz konusu olan yanlışlıklar düzeltilmeye çalışılmıştır. Büyük Selçuklular Arap-İslâm dünyasının, Türkiye Selçukluları ise Moğolların astronomi anlayışının etkisi altında kalmışlardır. Selçuklular Dönemi'nde açılan çeşitli rasathânelerde astronomi gözlemleri ve takvim çalışmaları yapılmıştır.

Above all, the first civilization cared about the science of astronomy in order to regulate their religious, economic and political activities. The science of astronomy aims the needs and practive in the Eastern Civilization. İn the Western Civilizations it come from the apprehension of cosmology. The place-centered universe apprehension of Aristotle and Ptolemy (Ptolemeios) is adopted as prevalent and acceptable idea. İn the İslâmic Era the universe apprehension of Aristotle and Ptolemy (Ptolemeios) was accepted. However, the deficiency in this apprehension was tried to be completed and the mistakes to be corrected However, in the Period of Seljuks, there wasn't many changes in the astronomy apprehension that the first civilizations and İslâmic world adopted. The universe and astronomy apprehension of Aristotle and Ptolemy (Ptolemeios) was maintained. Nevertheles, the Works of Ptolemy (Ptolemeios) were criticized in this era, and the wrongs in question were tried to be correted. The Great Seljuks were impressed by the astronomy apprehension of Arab-İslâmic World and the Turkish Seljuks were impressed by woks the Moghul's. Besides, there were studies of calender Works and astronomy observation in the various observatories opend in Seljuk's Era
Astronomy in the Seljuks period
Keywords: Tarih